A case of resistant scleral thinning following uneventful pterygium surgery: A case report and a literature review. (June 2022) - Sultan, Dana; Alnema, Othman; Sultan, Mohamad Nour; Zahlouk, Nadim; Kayyali, Ammar
Abstract: Introduction: We describe the management of a scleral thinning after uneventful pterygium surgery, it is an uncommon complication; in addition, we have reviewed similar published cases in the literature. Presentation of case: A 48-year-old woman presented with thinning sclera in the first week after pterygium excision surgery. Conservative treatment was the first line in the management. There was no improvement for two weeks, so we decided to do a rotational flap. We put a scleral dellen diagnosis by excluding other etiologies. The condition was successfully managed, the thinning sclera healed completely. Scleral and conjunctival re-surfacing was observed. Clinical discussion: Scleral dellen is an early and rare postoperative complication after pterygium surgery. The diagnosis is confirmed after excluding other causes of scleral thinning. The exact pathophysiology of it is not determined yet, many authors described probable explanation in their published cases. We did a comprehensive review of similar cases with their management. Conclusions: Scleral dellen is uncommon complication after pterygium surgery, its diagnosis depends on exclusion. The management can be conservative. However, if no progression was detected do not hesitate going for surgical closure. Highlights: We describe the management of scleral thinning after uneventful pterygium surgery. Scleral dellen is uncommon complication after pterygium surgery. The diagnosis of Scleral dellen is confirmed after excluding other causes of scleral thinning. The management can be conservative. However, if no progression was detected, surgical closure is the final management.